La cosmología de la reditio en Tomás de Aquino : un examen en torno a la noción de materia - Larre, Olga Lucía (Sapientia, 2015)
It is our purpose in the present work to analyze the notion of Aquinas’ matter, in his Hexaëmeron included in the Commentary on the Sentences of Peter Lombard (II Sent., dist. 12-15). His commentary on Lombard is an occasion not only for explaining Genesis and for closely examining Saint Augustine’s understanding; but also for offering the opportunity to interpret Aristotle, and to present his doctrine of matter through a dialogue with Avicenna, Averroes, Avicebron and others contemporary philosophers. This attitude shows Doctor Communis as a reader of his predecessors and contemporaries. It is clear that he is perfectly aware of the current debate and wants to situate his ideas in a broader context. His fundamental positions are already taken and the pillars of his doctrine, configured.